Transcriptomic analysis of differentially expressed genes in the floral transition of the summer flowering chrysanthemum - Ren, Liping (BMC Genomics, 2016)
BACKGROUND: Chrysanthemum is a leading cut flower species. Most conventional cultivars flower during the fall, but the Chrysanthemum morifolium ‘Yuuka’ flowers during the summer, thereby filling a gap in the market. To date, investigations of flowering time determination have largely focused on fall-flowering types. Little is known about molecular basis of flowering time in the summer-flowering chrysanthemum. Here, the genome-wide transcriptome of ‘Yuuka’ was acquired using RNA-Seq technology, with a view to shedding light on the molecular basis of the shift to reproductive growth as induced by variation in the photoperiod. RESULTS: Two sequencing libraries were prepared from the apical meristem and leaves of plants exposed to short days, three from plants exposed to long days and one from plants sampled before any photoperiod treatment was imposed. From the ~316 million clean reads obtained, 115,300 Unigenes were assembled. In total 70,860 annotated sequences were identified by reference to various databases. A number of transcription factors and genes involved in flowering pathways were found to be differentially transcribed. Under short days, genes acting in the photoperiod and gibberellin pathways might accelerate flowering, while under long days, the trehalose-6-phosphate and sugar signaling pathways might be promoted, while the phytochrome B pathway might block flowering. The differential transcription of eight of the differentially transcribed genes was successfully validated using quantitative real time PCR. CONCLUSIONS: A transcriptome analysis of the summer-flowering cultivar ‘Yuuka’ has been described, along with a global analysis of floral transition under various daylengths. The large number of differentially transcribed genes identified confirmed the complexity of the regulatory machinery underlying floral transition. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-3024-4) contains supplementary material, which is available to authorized users.